Measurement of the Concentration of Potential Quality of Life in Local Communities - Tomaš, Rajko (Social indicators research, 2022)
Quality of life is an individual evaluation of the objective conditions in which a person lives. Objective living conditions determine the potential quality of life, which through individual valorisation becomes the quality of life in the full sense. In this paper, we present a method for measuring potential quality of life with a synthetic index of relative concentration ( SIRC ) that we have developed starting from the logical basis of the Herfindahl index. The SIRC measures the impact on quality of life due to the unequal distribution of objective living conditions among members of the same community. It transforms the original data on the inequality of the distribution of objective living conditions, generating appropriate weights, into indicators of the concentration of potential quality of life. Based on the obtained SIRC values, the categorization and ranking of the potential quality of life for the analyzed subjects that make up the same community is performed. The practical application of SIRC in the research of potential quality of life for 48 municipalities of the Republic of Srpska based on 34 indicators that show objective living conditions in municipalities are presented.